SciVee 2010
DOI: 10.4016/18407.01
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Providing Online Care in a Primary Care Setting

Abstract: OBJECTIVE:To study the use of e-visits in a primary care setting. PATIENTS AND METHODS:A pilot study of using the Internet for online care ("e-visits") was conducted in the Department of Family Medicine at Mayo Clinic in Rochester, MN. Patients in the department preregistered for the service, and then were able to use the online portal for consultations with their primary care physician. Use of the online portal was monitored and data were collected from November 1, 2007, through October 31, 2009. RESULTS:Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
1
20
1
1
Order By: Relevance
“…Interestingly, these were mainly reported before the timeframe of our review, suggesting a loss of research interest for unclear reasons 35. Several recent studies have examined automated patient interviewing in specialised settings including home,36 emergency department waiting rooms37 38 and online visits in primary care 39. One study found that physician-acquired history and computer-based systems each elicited important information that the other missed,40 reaffirming the role of technology in complementing rather than replacing the physician-acquired history.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, these were mainly reported before the timeframe of our review, suggesting a loss of research interest for unclear reasons 35. Several recent studies have examined automated patient interviewing in specialised settings including home,36 emergency department waiting rooms37 38 and online visits in primary care 39. One study found that physician-acquired history and computer-based systems each elicited important information that the other missed,40 reaffirming the role of technology in complementing rather than replacing the physician-acquired history.…”
Section: Resultsmentioning
confidence: 99%
“…Overall use was judged by clinicians to be appropriate with a minority of e-consultations resulting in a subsequent face-to-face encounter (n=3 studies) 34 85 110. After an early peak in email volume there is some evidence that the level falls back 127.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies outlined a number of novel technologies that had been introduced including providing links to X-ray and scan images34 70 98; automated test result tracking,80 text messaging question and answer service125; portals that use a code number or pictures of medications to avoid medication names being displayed41; and web-based triage 36. Many of the portals were carefully designed to deliver full or partial online access87 96 and some required complex technical development linking different systems, for example to provide access to pathology results and X-ray reports or images 70 98.…”
Section: Resultsmentioning
confidence: 99%
“…16,17,18 This study evaluated the feasibility and scope of de novo real-time primary care and urgent care-type visits delivered via a voice-and-video-over-Internet protocol. We were able to assess the feasibility of this type of online visit by answering several questions through this descriptive study: the demographic characteristics of patients using online visits in a community setting; the self-selected scope of care for which patients schedule a visit; the ability of healthcare professionals to successfully complete online visits and comply with protocols for these types of visits; the utilization of laboratory tests, radiology studies and prescriptions written during these visits; and the proportion of online visits that trigger recommendations for in-person visits based on protocols or providers' clinical judgment or need for a hands-on physical exam.…”
Section: Discussionmentioning
confidence: 99%
“…13 To our knowledge, all prior studies of telemedicine have analyzed encounters with established patients, or those in which a provider or trained individual acts as an intermediary between the patient and another provider, 14,15 or the use of highly structured, asynchronous e-visits through a patient portal. [16][17][18] Here we present the first description of the use of multimedia voice and video telemedicine in the provision of real-time primary and urgent care involving direct evaluation of new and return patients who self-initiated first contact with a healthcare provider through online scheduling at a private, neighborhood-based healthcare system in a large urban area.…”
Section: Introductionmentioning
confidence: 99%